Soy isoflavone supplementation tends to improve specific immune responses in postmenopausal women - Wratsangka, Raditya (Faculty of Medicine, Trisakti University, 2011)
Immune dysfunction in postmenopausal women tends to decrease health-related quality of life (HRQoL). The present study’s objective was to evaluate the effect of daily supplementation of 100 mg soy isoflavones on specific immune responses among healthy postmenopausal women. The study design was a community-based double blind randomized controlled trial involving 60 healthy postmenopausal women, aged between 48–60 years, in the Mampang Prapatan district of South Jakarta. Participants were randomized to receive either 100 mg soy-isoflavone + 500 mg calcium (intervention group) or 500 mg calcium only (control group). Both supplements were taken daily for 12 weeks, from January to April 2010. Specific immune responses (measured by serum Ig G and CD4+) were assessed at baseline and after supplementation. Statistical analysis using independent t-test was performed to evaluate the effect of soy isoflavone supplementation on specific immune responses. Fifty-six (93.3%) participants completed the study without any significant side-effects or adverse events. Daily supplementation of 100 mg soy isoflavones for 12 weeks did not significantly increase the humoral specific immune response (p=0.242), but tended to improve the cellular specific immune response (p= 0.850). Other findings of this study were that soy isoflavone supplementation tends to improve specific immune responses in postmenopausal women with normal body mass index and adequate daily dietary isoflavone intakes. Short-term soy isoflavone supplementation is unable to improve the humoral and cellular specific immune responses in postmenopausal women aged 48 to 60 years.